Hawaiian larval stomatopods: molecular and morphological diversity - Steck, Mireille; Winnicki, Elizabeth; Kobayashi, Donald R.; Whitney, Jonathan L.; Ahyong, Shane T.; Porter, Megan L. (Zootaxa, 2022)
Estimating stomatopod species diversity using morphology alone has long been difficult; though over 450 species have been described, new species are still being discovered regularly despite the cryptic behaviors of adults. However, the larvae of stomatopods are more easily obtained due to their pelagic habitat, and have been the focus of recent studies of diversity. Studies of morphological diversity describe both conserved and divergent traits in larval stomatopods, but generally cannot be linked to a particular species. Conversely, genetic studies of stomatopod larvae using DNA barcoding can be used to estimate species diversity, but are generally not linked to known species by analyses of morphological characters. Here we combine these two approaches, larval morphology and genetics, to estimate stomatopod species diversity in the Hawaiian Islands. Over 22 operational taxonomic units (OTUs) were identified genetically, corresponding to 20 characterized morphological types. Species from three major superfamilies of stomatopod were identified: Squilloidea (4 OTUs, 3 morphotypes), Gonodactyloidea (9, 8), and Lysiosquilloidea (6, 7). Among these, lysiosquilloids were more diverse based on larval morphotypes and OTUs as compared to previously documented Hawaiian species (3), while squilloids had a lower diversity of species represented by collected larvae as compared to the seven species previously documented. Two OTUs / morphotypes could not be identified to superfamily as their molecular and morphological features did not closely match any available information, suggesting they belong to poorly sampled superfamilies. The pseudosquillid, Pseudosquillana richeri, was discovered for the first time from Hawaiʻi. This study contributes an updated estimate for Hawaiian stomatopod diversity for a total of 24 documented species, provides references for identification of larval stomatopods across the three major superfamilies, and emphasizes the lack of knowledge of species diversity in more cryptic stomatopod superfamilies, such as Lysiosquilloidea.